COMMON SIZE ANALYSIS OF THE FINANCIAL STATEMENTS OF BSI (BANK SYARIAH INDONESIA ) PERIOD 2020–2022 - Boonmaloet, Monthita (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
This study analyzes the financial structure of Bank Syariah Indonesia (BSI) for the period 2020–2022 using the common size analysis method. This approach is employed to examine the proportional composition of assets, liabilities, income, and operating expenses, offering clearer insights into financial trends within Islamic banking. The analysis is conducted within the framework of Justicia Economica, which emphasizes equitable allocation of funds and efficient management of financial resources. The study adopts a descriptive quantitative method based on BSI’s officially published annual financial statements. Each financial item is converted into a percentage of total assets or total revenue to identify structural changes and compare financial proportions across the observed years. The results show that customer financing consistently represents the largest component of BSI’s assets, rising from 66.3% in 2020 to 69.7% in 2022. On the liabilities side, Third-Party Funds (DPK) remain the dominant source of funding, contributing over 82% annually and reflecting strong public confidence. Income is primarily derived from Sharia-compliant financing instruments, such as murabahah and ijarah, with non-financial income experiencing notable growth. Operating expenses increased throughout the period, contributing to a decline in pre-tax profit from 17.2% to 15.8%. This study provides a structured financial profile of BSI through common-size analysis and offers insights for policymakers and practitioners to enhance efficiency, strengthen capital structure, and optimize income diversification to support the sustainability of Islamic financial institutions.